Analisis Pembelajaran Berdiferensiasi Berbasis Joyful Learning dalam Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Rendi Prilandi; Haris Steven Siregar; Muhammad Hafiz Ermawan; Putri Febrianti Purba; Assha Uli Handayani Hasibuan; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to analyze the implementation of a differentiated curriculum based on joyful learning in enhancing the learning motivation of elementary school students. The method used is a descriptive qualitative approach through a literature review by examining various relevant scientific sources over the past five years (2021–2025). The research process includes the collection, selection, analysis, and synthesis of data from national and international journals, books, and scientific articles using content analysis techniques. The research findings indicate that the integration of differentiated learning and joyful learning can result in a more dynamic, engaging, and student-centered learning process. This approach has been proven to enhance student engagement, activity, and learning motivation by adapting learning content, processes, and products to students’ needs, interests, and learning styles. Additionally, the use of innovative learning technologies, game-based activities, and collaborative learning will enhance the effectiveness of instruction. The teacher’s role as a facilitator is crucial to the success of this implementation. Thus, a differentiated curriculum based on joyful learning is an effective and relevant strategy for enhancing student motivation and creating meaningful and inclusive learning experiences.